2015
DOI: 10.3389/fnbeh.2015.00102
|View full text |Cite
|
Sign up to set email alerts
|

Pro-social 50-kHz ultrasonic communication in rats: post-weaning but not post-adolescent social isolation leads to social impairments—phenotypic rescue by re-socialization

Abstract: Rats are highly social animals and social play during adolescence has an important role for social development, hence post-weaning social isolation is widely used to study the adverse effects of juvenile social deprivation and to induce behavioral phenotypes relevant to neuropsychiatric disorders, like schizophrenia. Communication is an important component of the rat's social behavior repertoire, with ultrasonic vocalizations (USV) serving as situation-dependent affective signals. High-frequency 50-kHz USV occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
44
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 91 publications
7
44
3
Order By: Relevance
“…The USVs recorded in all groups were in the 50kHz range which occur in social, appetitive situations, during tickling and sexual behaviour thought to reflect positive affective state in rats (Brudzynski, 2013;Seffer et al, 2015). The increase in USVs in the socially isolated rats may reflect an increased motivation for social interaction although this was not accompanied by an increase in total social interaction compared to group-housed rats.…”
Section: European Neuropsychopharmacology 19mentioning
confidence: 82%
See 1 more Smart Citation
“…The USVs recorded in all groups were in the 50kHz range which occur in social, appetitive situations, during tickling and sexual behaviour thought to reflect positive affective state in rats (Brudzynski, 2013;Seffer et al, 2015). The increase in USVs in the socially isolated rats may reflect an increased motivation for social interaction although this was not accompanied by an increase in total social interaction compared to group-housed rats.…”
Section: European Neuropsychopharmacology 19mentioning
confidence: 82%
“…Consistent with the current findings the increase in avoidance and decrease in following behaviour produced by sub-chronic PCP administration to adult rats was also reversed by cariprazine (Neill et al, 2015). Using an identical PCP/isolate paradigm we found that clozapine (at doses which reversed the NOR deficit) was unable to restore the pro-social behavioural deficit (McIntosh et al, 2012), consistent with clozapine's limited efficacy to treat the negative symptoms of schiziophrenia and supporting the potential translational value of this test.The USVs recorded in all groups were in the 50kHz range which occur in social, appetitive situations, during tickling and sexual behaviour thought to reflect positive affective state in rats (Brudzynski, 2013;Seffer et al, 2015). The increase in USVs in the socially isolated rats may reflect an increased motivation for social interaction although this was not accompanied by an increase in total social interaction compared to group-housed rats.…”
mentioning
confidence: 82%
“…To exclude the effects of contaminated RNA-hybiridsed L1 DNA, 22 we re-evaluated copy numbers of L1-ORF2 after treating DNA samples with RNaseH and exonuclease 1, but obtained similar results (Mann-Whitney U test, ORF2 / 5S rDNA: P D 0.02, ORF2 / b-globin: P D 0.01, Figure S1). Additional analysis of the DNA samples of mice at 15,18,20, and »55 weeks after birth indicated that the L1 copy numbers were maximal at 8 weeks after birth (Fig. 1A, left panel).…”
Section: Increased Copy Numbers Of L1 In the Hippocampus During Maturmentioning
confidence: 99%
“…To study chronological changes in the L1-ORF2 copy numbers, 6 groups of mice at various ages (3,8,15,18,20, and »55 weeks) were analyzed. Six mice from each group (3 males and 3 females) and 6 8-week-old mice used for validation (3 males and 3 females) were deeply anaesthetised and perfused transcardially with cold 4% paraformaldehyde in phosphate-buffered saline (PBS), and genomic DNA was extracted from the right and left hippocampi and the prefrontal cortex.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation